PROBLEM OF QUALITY OF EDUCATIONAL PROGRAMS: AUTOMATED ASSESSMENT METHOD - Logachev, Maxim; Kozhevnikov, Evgeny; Brusentsova, Liliya; Mudarisov, Ramil; Imangulov, Aydar (Revista Inclusiones, 2020)
The article substantiates a relevant problem of education in Russia: an objective assessment of the quality of educational programs. The article substantiates the need to develop a quality system of educational programs for educational organizations in Russia. To do this, the analysis of the main normative documents regulating the educational process is carried out. These documents primarily include the Federal State Educational Standard and the professional standard. The analysis of the content of educational programs used in the activities of educational organizations is carried out. On its basis, the significance of its elements and their connection with each other is determined. An assessment package is developed to assess the compliance of each element. This allows evaluating the content in the appropriate educational program. The composition of such an assessment complex is formed based on a survey of experts specializing in the organization, control or audit of the educational process. Using this expert survey, the significance of each element is determined at the level of its corresponding criteria and the educational program as a whole. The mechanism for determining the weight values of each element for a separate level of the educational program model is presented in detail. To calculate the significance of each element, the Kendall concordance coefficient is determined and the result is evaluated using Pearson’s chi-squared test with a set level of accuracy. It is found that the obtained values meet the requirements for use in the methodology for determining the quality of the educational program. The article presents the obtained values for each level of the hierarchical model of the educational program.